2019
DOI: 10.1101/666578
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biased Signaling: Distinct Ligand-directed Plasma Membrane Signalosomes Using a Common RGS/G protein Core

Abstract: Abbreviations: Arabidopsis thaliana Regulator of G Signaling (AtRGS1), Clathrin-Mediated 43 Endocytosis (CME), Sterol-Dependent Endocytosis (SDE), Total Internal Reflection 44 Fluorescence Microscopy (TIRF), Clathrin Light Chain (CLC), Flotilin 1 (FLOT1), 45 Vacuolar Protein Sorting 26 (VPS26) 46 SUMMARY 47 Biased signaling occurs when different ligands that are directed at the same receptor launch 48 different cellular outcomes. Because of their pharmacological importance, we know the most 49 about biased lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 122 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…These studies indicate that the MAPK cascade could act as a downstream effector of G protein signalling (Lieberherr et al 2005; Su et al 2015). Interestingly, recent studies found flg22 initiates AtRGS1 endocytosis via clathrin‐mediated endocytosis (CME) to induce a MAPK cascade known to drive transcriptional reprogramming (Ross‐Elliott et al 2020). Whereas glucose induces endocytosis of AtRGS1 via sterol‐dependent endocytosis (SDE) to induce genes transcriptional change independent of the MAPK cascade (Ross‐Elliott et al 2020).…”
Section: G Proteins In Plant Biotic Stress Responsementioning
confidence: 99%
See 1 more Smart Citation
“…These studies indicate that the MAPK cascade could act as a downstream effector of G protein signalling (Lieberherr et al 2005; Su et al 2015). Interestingly, recent studies found flg22 initiates AtRGS1 endocytosis via clathrin‐mediated endocytosis (CME) to induce a MAPK cascade known to drive transcriptional reprogramming (Ross‐Elliott et al 2020). Whereas glucose induces endocytosis of AtRGS1 via sterol‐dependent endocytosis (SDE) to induce genes transcriptional change independent of the MAPK cascade (Ross‐Elliott et al 2020).…”
Section: G Proteins In Plant Biotic Stress Responsementioning
confidence: 99%
“…Interestingly, recent studies found flg22 initiates AtRGS1 endocytosis via clathrin‐mediated endocytosis (CME) to induce a MAPK cascade known to drive transcriptional reprogramming (Ross‐Elliott et al 2020). Whereas glucose induces endocytosis of AtRGS1 via sterol‐dependent endocytosis (SDE) to induce genes transcriptional change independent of the MAPK cascade (Ross‐Elliott et al 2020). Although MAPK activation is recognized as a defence marker in plant immunity, how G protein complex triggers activation of the MAPK cascade still needs further exploration (Su et al 2015).…”
Section: G Proteins In Plant Biotic Stress Responsementioning
confidence: 99%